A Conceptual Approach to the Development of the Cross-Border Model of Sustainable Development of Regions in Times of War - Lesya Korolchuk (Studia Regionalne i Lokalne)
In the context of the war in Ukraine, the author defines the cross-border model of sustainable development of regions as an effective one, which can be used to adopt the EU’s progressive experience in achieving the Sustainable Development Goals, adapt it, and timely transfer it to the internal regions in the post-war recovery of our country. According to the conceptual approach, the ER-cross-border model of sustainable development of regions is developed based on the analysis of the subject area of sustainable regional development, cross-border cooperation of regions for sustainable development, and cross-border cooperation of regions for sustainable development in times of war.